Neural Correlates of Morphological Processing: Evidence from Chinese - Zou, Lijuan; Packard, Jerome L.; Xia, Zhichao; Liu, Youyi; Shu, Hua (Frontiers in Human Neuroscience, 2016)
Morphological decomposition is an important part of complex word processing and the left inferior frontal gyrus (L-IFG) has been shown to be a key brain area involved in morphological processing in alphabetic languages. Chinese morphological processing requires a comprehensive consideration of phonological, orthographic and morphemic information. But it had been unclear whether the neural mechanisms underlying morphological processing in alphabetic languages would also be found for Chinese. To answer this question, an explicit auditory morphological judgment task was used in an fMRI experiment to investigate the neural basis of morphological processing in Chinese compound words. Results demonstrated that the L-IFG to be a core area, consistent with research in alphabetic languages. More importantly, a broad network consisting of the L-MTG, the bilateral STG and the L-FG that taps phonological, orthographic, and semantic information was found to be involved in Chinese morphological processing. These results provide evidence that the L-IFG plays an important role in morphological processing even in languages that are typologically different.